Intra-generic diversity in Paracholeothrips, an Australian genus of domicile-building phlaeothripine Thysanoptera on Acacia phyllodes - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2025)
Two new species are described in the Acacia-associated genus Paracholeothrips each of which is readily distinguished by remarkable autapomorphies. P. morrisi sp. nov. bears a pair of prominent horns laterally on the head. P. phillipsi sp. nov. has the head, pronotum, prosternal ferna and pelta all greatly elongate. The intra-generic structural diversity is illustrated, and a key provided to the seven species now recognised.